INNOVATIVE DIRECTIONS OF ENSURING EMPLOYMENT IN IMPROVING THE POPULATION'S STANDARD OF LIVING IN THE REGION - Orozov Azamat Otaboyevich; Matniyozova Zilola Shamurod qizi (International Journal of Economic Integration and Regional Competitiveness, 2026)
Objective: This article analyzes the innovative directions of ensuring employment, one of the most important factors in improving the living standards of the region's population. Method: It examines the current state of the regional labor market and the trends observed within it, the new forms of employment emerging under the influence of the digital economy and artificial intelligence technologies, the mechanisms encouraging entrepreneurship and self-employment, as well as the proposals and recommendations developed based on the advanced experience of foreign countries. Results: The findings indicate that digitalization, artificial intelligence technologies, entrepreneurship, and self-employment create new employment opportunities and contribute to improving the living standards of the regional population. Novelty: This study offers an integrated employment development approach by combining digital transformation, artificial intelligence, entrepreneurship support, self-employment mechanisms, and relevant international practices within the regional labor market.